CONTROL OF ELECTRIC SHIPS’ PROPULSION MOTORS WHEN MOVING ON CURVILINEAR TRAJECTORY - V. A. Yarovenko (National Technical University "Kharkiv Polytechnic Institute", 2020)
Purpose. The aim of the work is to search for the optimal control of the electric ships’ propeller motors (PM) while moving on curvilinear trajectory. The indices characterizing the vessel were selected as the criteria of optimality. Methodology. Optimal control laws of PM providing electric ships’ best maneuverability can be found by joint consideration of the electric propelling plant (EPP), propellers and hull. Results. A method of calculating the transient regimes of the electric ships’ propulsion complexes during maneuver has been developed. A new method of forming the PM control laws is proposed. The nature of the target functions is revealed and a method of optimizing the parameters of control signals is developed. Optimization calculations have been carried out and the optimal control of the electric ships’ propeller motors when moving along curvilinear trajectory has been found. Optimization has been carried out by the criterion of minimum energy consumption and by the criterion of minimum ship’s distance. The optimization efficiency is illustrated. Scientific novelty. The method of searching for the optimal control laws is constructed according to the system principle, which allows optimizing the control of the propulsion motors by the final result. Practical value. The proposed recommendations can be used in the design of electric propelling plants and in their operation.